Mekanisme Tata Kelola dan Penghindaran Pajak: Pengaruh Kepemilikan Institusional, Dewan Komisaris Independen, dan Komite Audit - Budiadnyani, Ni Putu; Kleff, Ayu Agnes; Aprilyani Dewi, Putu Pande R; Ayu Pramita Indraswari, I Gusti Agung (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2025)
This study examines the effects of institutional ownership, independent board of commissioners, and audit committee on tax avoidance practices among publicly-traded companies in Indonesia. The findings aim to provide insights for policymakers and regulators to enhance tax compliance and ensure companies fulfill their tax obligations. The study employs a quantitative approach, utilizing secondary data from the financial reports of Indonesian Stock Exchange in the banking sector. The research aims to investigate how these key corporate governance mechanisms influence tax avoidance behavior, with the ultimate goal of informing policies and regulations to promote greater tax compliance and responsible corporate practices. By exploring the relationship between these governance factors and tax avoidance, the study seeks to contribute to the understanding of how to foster a more transparent and accountable tax environment among publicly-traded companies in Indonesia. The study also aims to shed light on the role of corporate governance in shaping tax practices, which can inform the development of policies and regulations to promote ethical and responsible tax management among publicly-traded companies in Indonesia.